The Well-Being Benefits of Person-Culture Match Are Contingent on Basic Personality Traits - Jochen E. Gebauer; Jennifer Eck; Theresa M. Entringer; Wiebke Bleidorn; Peter J. Rentfrow; Jeff Potter; Samuel D. Gosling (Psychological Science, 2020)
People enjoy well-being benefits if their personal characteristics match those of their culture. This person-culture match effect is integral to many psychological theories and—as a driver of migration—carries much societal relevance. But do people differ in the degree to which person-culture match confers well-being benefits? In the first-ever empirical test of that question, we examined whether the person-culture match effect is moderated by basic personality traits—the Big Two and Big Five. We relied on self-reports from 2,672,820 people across 102 countries and informant reports from 850,877 people across 61 countries. Communion, agreeableness, and neuroticism exacerbated the person-culture match effect, whereas agency, openness, extraversion, and conscientiousness diminished it. People who possessed low levels of communion coupled with high levels of agency evidenced no well-being benefits from person-culture match, and people who possessed low levels of agreeableness and neuroticism coupled with high levels of openness, extraversion, and conscientiousness even evidenced well-being costs. Those results have implications for theories building on the person-culture match effect, illuminate the mechanisms driving that effect, and help explain failures to replicate it.
Keywords: 300; person-culture match; culture; basic personality traits; Big Two; Big Five; open data; open materials